A patient with an acute confusional state - Baker, Graham (BMJ Publishing Group, 2010)
A 49-year-old male presented in an acutely confused state. His examination and basic blood tests were unremarkable. He was started on intravenous aciclovir and an MRI brain scan showed changes consistent with limbic encephalitis. Serum antibodies including para-neoplastic auto-antibodies and cerebrospinal fluid studies were arranged along with a full body CT scan to look for malignancy. All antibody tests returned negative and the CT scan ruled out the presence of malignancy. The patient improved following treatment with intravenous immunoglobulin and was discharged. Follow-up imaging showed significant radiological improvement. He has been able to return to work and repeat CT scans have failed to find evidence of malignancy. A rare and treatable cause for his illness was found. It is worth considering limbic encephalitis when facing a confused patient especially in the young and middle-aged population.